Attitude sensor and actuator interfacing for micro-satellites - Dlamini, Zamokwakhe P. (Zamokwakhe Peacemaker) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2002.